2022
DOI: 10.3390/plants11141874
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Niche Modeling of Water Lily (Nymphaea L.) Species in Australia under Climate Change to Ascertain Habitat Suitability for Conservation Measures

Abstract: The International Panel on Climate Change (IPCC) projects a global temperature rise of 4.3 ± 0.7 °C by 2100 and an extinction of 8.5% in one out of every six species. Australia’s aquatic ecosystem is no exception; habitat loss, fragmentation, and loss of biodiversity are being experienced. As the center for Nymphaea species distribution, it presents the culturally, ecologically, and scientifically important genus as the best candidate for habitat suitability assessment in climate change, whose habitat suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In addition, the distribution range of I. nanchuanensis is projected to shrink in the future periods, especially the 2070s, with the total suitable area being reduced the most under RCP6 and the least under RCP4.5, which is similar to the findings of other studies on rare and endangered species in China, such as ginkgo (Ginkgo biloba) and Taiwan fir [90,91] . This is closely related to the phenomenon of climate warming in the future, with studies finding a global temperature increase of 1.3°C by 2050 and a minimum global temperature increase of 2.2°C by 2070 [5,92] . This study found that the optimum range for the hottest monthly minimum temperature (Bio6), the most important climatic factor affecting I. nanchuanensis, is −30°C to 25°C, and that extreme weather and global warming have made it difficult for the species to survive better locally, which is one of the main reasons for the migration of I. nanchuanensis to the northwest in the coming period.…”
Section: Potential Distribution Area Changes and Conservation Of Ilex...mentioning
confidence: 92%
“…In addition, the distribution range of I. nanchuanensis is projected to shrink in the future periods, especially the 2070s, with the total suitable area being reduced the most under RCP6 and the least under RCP4.5, which is similar to the findings of other studies on rare and endangered species in China, such as ginkgo (Ginkgo biloba) and Taiwan fir [90,91] . This is closely related to the phenomenon of climate warming in the future, with studies finding a global temperature increase of 1.3°C by 2050 and a minimum global temperature increase of 2.2°C by 2070 [5,92] . This study found that the optimum range for the hottest monthly minimum temperature (Bio6), the most important climatic factor affecting I. nanchuanensis, is −30°C to 25°C, and that extreme weather and global warming have made it difficult for the species to survive better locally, which is one of the main reasons for the migration of I. nanchuanensis to the northwest in the coming period.…”
Section: Potential Distribution Area Changes and Conservation Of Ilex...mentioning
confidence: 92%